ANALISIS KETERAMPILAN MEMBACA CEPAT DAN PEMAHAMAN BACAAN SISWA KELAS IV SDN 15 NANGA PINOH - Diana Natalia; Ahmad Khoiri; Eko Rudiyansah (STKIP Subang, 2026)
This study aimed to analyze the speed reading skills and reading comprehension of fourth-grade students at SDN 15 Nanga Pinoh. The study employed a descriptive qualitative approach. The subjects of the study were 15 fourth-grade students. Data were collected through reading tests, observation, interviews, and documentation. The data were analyzed through data reduction, data presentation, and conclusion drawing. The results showed that the students’ speed reading skills were generally in the moderate category. Of the 15 students, most achieved reading speeds between 100–200 words per minute (WPM), while a smaller number reached 200–300 WPM. Assessment of speed reading aspects indicated that students still experienced difficulties in pronunciation, pause usage, intonation, and reading fluency. In addition, reading comprehension levels varied among students, with some students achieving very good comprehension, while others remained in the moderate and low categories. These findings indicate that students’ speed reading skills and reading comprehension require continuous improvement through regular reading practice and appropriate instructional strategies. Therefore, teachers are expected to provide learning activities that support the development of speed reading and reading comprehension skills in elementary school students.